Complexity theory and the philosophy of education - Mason, Mark, 1959-; Wiley InterScience (Online service) (Chichester, West Sussex, U.K. ; Malden, MA : Wiley-Blackwell, 2008)
A collection of scholarly essays, Complexity Theory and the Philosophy of Education provides an accessible theoretical introduction to the topic of complexity theory while considering its broader implications for educational change.: Explains the contributions of complexity theory to philosophy of education, curriculum, and educational research; Brings together new research by an international team of contributors; Debates issues ranging from the culture of curriculum, to the implications of work of key philosophers such as Foucault and John Dewey for educational change; Demonstrates how socia.
Notes on Contributors; Foreword: Complexity and knowledge systems; 1 Complexity Theory and the Philosophy of Education; 2 Educational Philosophy and the Challenge of Complexity Theory; 3 What Is Complexity Theory and What Are Its Implications for Educational Change?; 4 Complexity and Education: Vital simultaneities; 5 Three Generations of Complexity Theories: Nuances and ambiguities; 6 Re-reading Dewey through the Lens of Complexity Science, or: On the creative logic of education; 7 Foucault as Complexity Theorist: Overcoming the problems of classical philosophical analysis.
Includes bibliographical references and index.
Print version record.
Keywords: Education -- Philosophy; Computational complexity; Education; Electronic books